Effect of methoxyflavones contained in Kaempferia parviflora on CRE-mediated transcription in PC12D cells. Issue 23 (1st December 2020) - Natsume, Noriyuki; Yamano, Aki; Watanabe, Akio; Yonezawa, Takayuki; Woo, Je-Tae; Yamakuni, Tohru; Teruya, Toshiaki
Graphical abstract: Abstract: The cAMP-response element (CRE) is critical in the formation of long-term memory. To prove the pharmacological effects of the methoxyflavones-rich residue (MRR) and its constituent methoxyflavones (1–9 ) extracted from the rhizomes of Kaempferia parviflora on the nervous system, we examined the effects of the MRR and methoxyflavones (1–9 ) on CRE-mediated transcription in PC12D cells. The MRR increased CRE-mediated transcription in PC12D cells. In addition, among methoxyflavones (1–9 ) isolated from MRR, compounds 1–4 increased CRE-mediated transcription. These results suggest that K. parviflora and methoxyflavone might be very useful materials for preventing and recovering from cognitive decline.